Bioclimatic Analysis of Vernacular Iranian Architecture - Pourvahidi, Parastoo (Eastern Mediterranean University (EMU), 2010)
Many factors are involved in the evolution of architectural styles around the world. In Iran, environmental and natural phenomena play a very important role in the regions inter-related cultural, economic and social infra-structures. Different settlements in Iran have diverse climate and cultures. Subsequently, for controlling the climate they created different design solutions. Climate has major effects on the buildings and the most critical is to understand how to control the climate with the buildings. Hence, it is essential to classify the climates for architectural purposes to understand Iranian vernacular architecture. Special importance of this research is that it studies the bioclimatic design principles in whole parts of Iran. Bioclimatic design in the buildings tries to maximize thermal comfort and minimize the buildings need for energy for heating and for cooling. This thesis will analyze the vernacular design principles of different regions of Iran by the means of bioclimatic concepts. Furthermore, this research by retrieving the climatic data from all Iranian Meteorological stations found the characteristic of each region and new bioclimatic charts achieved. Consistent with data plotted of new bioclimatic charts, this research found five different climates in Iran. By using these bioclimatic charts bioclimatic analysis on each region will be possible. Second stage of this thesis will discuss the characteristics of architecture and design principles of these five different climatic regions in Iran. Finally, at the third stage a comparison between the vernacular Iranian architecture and the vernacular architecture of the other countries will be made.
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2010. Supervisor: Prof. Dr. Mesut Özdeniz.
Keywords: Architecture; Architecture - Environmental aspects - Iran; Architecture and climate - Iran; Climate - Vernacular - Iran - Bioclimatic